Influence of American Society of Anesthesiologists Score on Oncologic Outcomes in Patients With Upper Tract Urothelial Carcinoma After Radical Nephroureterectomy: A Large-Sample Study in Two Institutions - Yuan, Yichu; Wang, Yiqiu; Zhang, Nan; Mao, Xiawa; Huang, Yiran; Huang, Jiwei; Ji, Na (Frontiers in Oncology, 2021)
Introduction As a research team of urologists and an anesthetist, we sought to investigate the prognostic significance of American Society of Anesthesiologists (ASA) score in patients with upper tract urothelial cancer (UTUC) after radical nephroureterectomy (RNU). ASA physical status (ASA-PS) classification not only was found to be associated with increased comorbidities but also independently factors for predicting morbidity and mortality. Accurate risk assessment was being particularly important for patients being considered for surgery. Methods Records for 958 patients with UTUC who underwent RNU were reviewed. Clinicopathologic variables, including ASA-PS, were assessed at two institutions. Overall survival (OS), cancer-specific survival (CSS), intravesical recurrence-free survival (IRFS), and metastasis-free survival (MFS) were estimated using the Kaplan–Meier method and Cox regression analyses. We measured the independent predictive value of ASA-PS for mortality by multivariate regression. Association of ASA-PS and clinicopathologic variables was assessed. Results The group of patients with ASA = 2/3 had a shorter 5-year OS (67.6% and 49.9%), CSS (72.9% and 58.1%), and MFS (75.1% and 58.5%). The median follow-up time was 39 months. Kaplan–Meier curves showed that the group with ASA = 2/3 had significantly poorer OS, CSS, and MFS. Adjusting for multiple potential confounding factors, multivariate analyses suggested that ASA score was an independent predictor of OS, CSS, and MFS (p = 0.004, p = 0.005, p < 0.001). Conclusion Higher ASA scores were independently associated with lower survival rate. This capability, along with its simplicity, makes it a valuable prognostic metric. It should be seriously referenced in UTUC patients being considered for RNU.